Transport morski w rozwoju zrównoważonym Unii Europejskiej - Salmonowicz, Henryk (Marine Transport in Sustainable Development of the European Union, 2008)
This article concerns the specifity of role and place of marine transport in the development of the European Union. The author describes the meaning of development and ekodevelopment, the creation of an idea of the European Union, proekological structure of the European Union and the special meaning of marine transport in this development of integrated group.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 11, s. 167-175